PERFORMA PRODUKSI UDANG VANAME (Litopenaeus vannamei) YANG DIBUDIDAYAKAN PADA TAMBAK SISTEM SEMI INTENSIF DENGAN APLIKASI PROBIOTIK - Titik Susilowati; Vivi Endar Herawati; Fajar Basuki; Tristiana Yuniarti; Diana Rachmawati; Suminto Suminto (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
The aimed of this research to effect probiotics influented on the growth, survival rates, production, productivity and FCR and water quality condition of Pacific white shrimp L. vannamei in pond under semi intensif system. Six of pond compartments each sized 2,000 m2 were stocked with PL-12 at the density of 15 fries/m2. Two treatmens of probiotics application in pond were tested, there were A). 0 mg/L probiotic and B).1.5 mg/L fermentation of probiotic. Each treatment was done in three replicated. On treatment probiotic applied weekly to the ponds started on the first week before shrimp stocking until harvested, while in treatment B probiotic application was mixedwith feed pelled then it was given to the cultured shrimp in the ponds. Result of the research showed that final shrimp body weight in treatment B tend to be higher compared to the treatment A. Absolut shrimp growth-rate in treatment B: 20.727 ± 0.042 g and treatment A :15.7 ± 0.016 g, Shrimp survival rate treatment A 0.432±0.0003 and treatment B : 0.79±0.0145. Production-rate of shrimp in treatment A: 203.627±0.083 kg/2000 m2 and treatment B : 504.489 kg/200 m2. Productivity of shrimp in treatment A : 0.1 kg/m2/period of plants dan perlakuan B: 0.25 kg/m2/period of plants. FCR of shrimp in treatment A 1.79±0.005 and treatment B : 1.42±0.003. Probiotics used in treatment B resulted in the enchancement of water quality condition (total organic matter, nitrat) compared to the treatment A ( 0 probiotics). This condition presumably resulted the highest shrimp production in treatment A.Keywords : production, Pacific white shrimp, probiotics.